Implementasi Kebijakan Pelayanan Perizinan Usaha Mikro Kecil Menengah Berbasis “Online Single Submission Risk Based Approach” (Oss Rba) Di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kabupaten Bintan - Dewi Safitri; Agus Hendrayady; Jamhur Poti (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The system (OSS RBA) is a platform for administering business licensing that is digital-based and has been issued for business actors who will carry out business activities assessed based on the level of risk of business activities. The purpose of this study is to find out the Application of the Policy Contents of Government Regulation No. 5 of 2021 Concerning the Implementation of Risk-Based Licensing Services for MSME Actors by the DPMPTSP of Bintan Regency. The related indicators in this study are: 1). Government Regulation, 2). Resources, 3). Communication, 4). Disposition or Attitude of Executors, 5). Assisted Services Clinic. This type of research uses a qualitative descriptive analysis technique with 8 informants. The results of the research (1) In Government Regulation No. 5 of 2021 the Bintan Regency Investment and One-Stop Services Service already has Standards, Goals and Targets in implementing the OSS RBA system. (2) Resources which include, Human resources that are adequate and have obtained BIMTEK in providing services to business actors, Financial Resources are still inadequate because DPMPTSP applies a budget priority scale for OSS RBA system policies, and Adequate Resources for Facilities and Infrastructure in the process implementation of OSS RBA system services. (3) Communication, DPMPTSP has collaborated with DKUPP Bintan Regency which has been granted derivative access rights for the OSS RBA system and socialization has been underway to business actors who are micro, small and medium enterprises